Comparison between contract-relax stretching and McKenzie neck exercise on decreasing pain of upper trapezius muscle in peeling onions workers - Zidni Imanurrohmah Lubis; Dianda Rizky Ayu Susanti; Atika Yulianti (Physical Therapy Journal of Indonesia, 2023)
Background: Upper trapezius muscle pain is caused by overuse of the neck, hand, and shoulder muscles with the same movement resulting in decreased oxygen supply to the muscles. The treatments that can be given are contract-relax stretching and Mckenzie neck exercise. Contract relax stretching aims to reduce pain with stretching techniques. McKenzie's neck exercise aims to relax muscles, reduce spasms and return the alignment of the neck to a normal position. Methods: This type of research is a pre-experimental study with two pretest and post-test design groups. This design uses two groups to compare the causal relationship between the independent and dependent variables. The research population was peeling onion workers at CV. Anita Jaya Sukses had upper trapezius muscle pain. The sample of this study is a member of the people that meets the inclusion and exclusion criteria with a total of 18 selections. The sampling technique used purposive sampling. The research instrument used is the numeric rating scale (NRS). Results: The Independent Sample T-Test showed that giving contract-relax stretching and McKenzie neck exercise had a significant value of 0.005 (p< 0.05), so H1 was accepted. Conclusion: There is a difference in the effect between contract-relax stretching and McKenzie neck exercise on reducing upper trapezius muscle pain in onion peel workers' CV. Anita Jaya Sukses and McKenzie's neck exercise has proven more effective.